If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2y + -1) * dx + -1(2x + y + -5) * dy = 0 Reorder the terms: (-1 + x + 2y) * dx + -1(2x + y + -5) * dy = 0 Reorder the terms for easier multiplication: dx(-1 + x + 2y) + -1(2x + y + -5) * dy = 0 (-1 * dx + x * dx + 2y * dx) + -1(2x + y + -5) * dy = 0 Reorder the terms: (-1dx + 2dxy + dx2) + -1(2x + y + -5) * dy = 0 (-1dx + 2dxy + dx2) + -1(2x + y + -5) * dy = 0 Reorder the terms: -1dx + 2dxy + dx2 + -1(-5 + 2x + y) * dy = 0 Reorder the terms for easier multiplication: -1dx + 2dxy + dx2 + -1dy(-5 + 2x + y) = 0 -1dx + 2dxy + dx2 + (-5 * -1dy + 2x * -1dy + y * -1dy) = 0 Reorder the terms: -1dx + 2dxy + dx2 + (-2dxy + 5dy + -1dy2) = 0 -1dx + 2dxy + dx2 + (-2dxy + 5dy + -1dy2) = 0 Reorder the terms: -1dx + 2dxy + -2dxy + dx2 + 5dy + -1dy2 = 0 Combine like terms: 2dxy + -2dxy = 0 -1dx + 0 + dx2 + 5dy + -1dy2 = 0 -1dx + dx2 + 5dy + -1dy2 = 0 Solving -1dx + dx2 + 5dy + -1dy2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'd'. d(-1x + x2 + 5y + -1y2) = 0Subproblem 1
Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0Subproblem 2
Set the factor '(-1x + x2 + 5y + -1y2)' equal to zero and attempt to solve: Simplifying -1x + x2 + 5y + -1y2 = 0 Solving -1x + x2 + 5y + -1y2 = 0 Move all terms containing d to the left, all other terms to the right. Add 'x' to each side of the equation. -1x + x2 + 5y + x + -1y2 = 0 + x Reorder the terms: -1x + x + x2 + 5y + -1y2 = 0 + x Combine like terms: -1x + x = 0 0 + x2 + 5y + -1y2 = 0 + x x2 + 5y + -1y2 = 0 + x Remove the zero: x2 + 5y + -1y2 = x Add '-1x2' to each side of the equation. x2 + 5y + -1x2 + -1y2 = x + -1x2 Reorder the terms: x2 + -1x2 + 5y + -1y2 = x + -1x2 Combine like terms: x2 + -1x2 = 0 0 + 5y + -1y2 = x + -1x2 5y + -1y2 = x + -1x2 Add '-5y' to each side of the equation. 5y + -5y + -1y2 = x + -1x2 + -5y Combine like terms: 5y + -5y = 0 0 + -1y2 = x + -1x2 + -5y -1y2 = x + -1x2 + -5y Add 'y2' to each side of the equation. -1y2 + y2 = x + -1x2 + -5y + y2 Combine like terms: -1y2 + y2 = 0 0 = x + -1x2 + -5y + y2 Simplifying 0 = x + -1x2 + -5y + y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
d = {0}
| 12/11=x/12 | | 2x-13-6x-2/5=1/3 | | -4=5-8(-4) | | (8-3x)(5x-x)=(3x-4)(x-6)-13 | | f(-4)=5-8x | | M-6=17 | | 3500=100+39x | | 100+39=3500 | | 2(4-g)-3(2g-6)=8(3g-1)-11(g-5) | | 4x+5y=2470 | | Y=cot(7x) | | 14+5n=14+3n | | x^2y+y^2x=14040 | | 2u+9=45 | | c=(a-u)/n | | ac=mc+n | | 12w^2+9w^3=0 | | 16-h^2+6hy+9y^2= | | x=(y-q)/m | | x=315/80 | | 315/80 | | X^3-3x-4x+12=0 | | -4+5+m=-3+7 | | -47+5+y=-2+4 | | 3y^2-22y+32=0 | | 7y-6y-4=5 | | 5x^2+45x-10=0 | | 7-1-(18-2)/8 | | 3y^2-22y-32=0 | | -1=3x^2-8x | | 2(x+1)+x=62 | | 1.32y+0.02=1.19+y |